Point de vue de l'artiste et assistant d'artiste : problématiques et expériences - Santiago Torres (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This text is the transcription of Santiago Torres’s talk at the first study day held on November 3, 2016, at the Villa des Arts (Paris). It goes along with the video of the presentation illustrating the case studies cited. Santiago Torres presents his thoughts from his experience as an artist's assistant of Julio Le Parc and Nicolas Schöffer. He details his vision of the concept of language as a key element in the understanding and restoration of these kinetic and cybernetic works; and wonders about the future of his own digital works.